Entwicklung und digitale Spaltung – Zusammenhänge und Prioritäten - Weber, Karsten (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
After a brief introduction of definitions and causes of the digital divide, particularly with regard to developing countries, the so-called “Simputer” and “One Laptop per Child” projects, which were designed to close the digital divide in developing countries, will be presented. It shall be argued that both projects are flawed by technological determinism and false assumptions about the impact of technology on social problems. As a conclusion it shall be predicted that the “One Laptop per Child” project is very likely to fail as the “Simputer” project already has failed.